Forced Displacement of and Potential Solutions for IDPs and Refugees in the Sahel : Burkina Faso, Chad, Mali, Mauritania and Niger - World Bank (Washington, DC, 2014)
The Sahel region has seen the forcible displacement of more than million persons as a result of conflict. Tackling displacement in the Sahel is critical for both poverty alleviation and stabilization, and only a development response will be adequate to the task. A development response to forced displacement in the Sahel requires a regional approach. Such an approach would have the benefits of being able to overcome challenges relating to cross-border movements, obtain commitments by host governments to support the prospects of displaced from neighboring countries, and facilitate common approaches, shared conceptualization and learning. The purpose of this scoping study on forced displacement is to contribute towards the formulation of a regional policy framework for sustainable solutions to displacement and towards the substantiation of a development response. The main challenges for the displaced populations include: i) livelihoods; ii) relations with host communities; iii) cohesion; iv) depletion of services; and v) governance. Measures to be taken to address the needs of these communities are: 1) improving the monitoring of population movement and knowledge on the locations, profiles and needs of the displaced, their host and return communities; 2) ensuring that the displaced and those affected by them can benefit from ongoing wider development investments in the region by designing 'displacement-sensitive' interventions; 3) strengthening services in affected areas through targeted regional investment programs; 4) employment creation and livelihood generation for those displaced; 5) delivering resources for the displaced in such a way that important outcomes are achieved; and 6) exploring the creative use of new technologies to extent information and development benefits to the displaced.